β-Lactam/β-Lactamase Inhibitor Combinations Non-Susceptible ESBL-Producing Enterobacteriaceae Bloodstream Infections: An Underestimated Clinical Entity - Zhang Y; Ni S; Hu H; Zhang S; Feng H; Ni L; Chen H; Yang Q; Yu M; Qu T (Infection and Drug Resistance, 2025)
Yan Zhang,1,* Shuangling Ni,2,* Hangbin Hu,3,* Sheng Zhang,4 Haiting Feng,4 Lingmei Ni,4 Hongchao Chen,5 Qing Yang,5 Meihong Yu,1 Tingting Qu1,4 1State Key Laboratory for Diagnosis and Treatment of Infectious Disease, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, Department of Infectious Disease, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of China; 2Infectious Disease Department, Lishui People’s Hospital, Lishui, 323000, People’s Republic of China; 3Department of Nutrition, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of China; 4Infection Control Department, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of China; 5Department of Laboratory Medicine, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, 310003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tingting Qu, The First Affiliated Hospital, College of Medicine, Zhejiang University, 79# Qingchun East Road, Hangzhou, 310001, People’s Republic of China, Email qutingting@zju.edu.cn Meihong Yu, The First Affiliated Hospital, College of Medicine, Zhejiang University, 79# Qingchun East Road, Hangzhou, 310001, People’s Republic of China, Email Y8m8h@163.comBackground: To describe the clinical and molecular characteristics of β-lactam/β-lactamase inhibitor combinations (BLBLIs) non-susceptible ESBL–producing Enterobacteriaceae (BnESBL-E) bloodstream infections (BSIs).Methods: A cohort study was performed with ESBL-E-BSI cases from 2017 to 2019 in East China. Clinical characteristics, risk factors, and all-course mortality were evaluated. Whole-genome sequencing and antibiotic susceptibility testing were performed.Results: Among the 187 patients with ESBL-E-BSI, 39.57% (74/187) had BnESBL-E-BSI. Nosocomial infections constituted 63.51% of BnESBL-E-BSIs, and 39.19% of cases originated from intra-abdominal sources. Risk factors for BnESBL-E-BSI included BLBLIs exposure within the preceding 3 months, ICU admission within the last 3 months, and the duration of hospital stay prior to BSI. Notably, a urinary source of bacteremia emerged as a protective factor against BnESBL-E-BSI(OR, 0.177; 95% CI, 0.049– 0.647; p=0.009). BnESBL-E-BSIs were associated with a higher 28-day mortality compared to BLBLIs-susceptible cases (31.08%vs.16.81%; p=0.031). Multivariate analysis identified the Pitt bacteremia score, CRP level, and hospitalization within the preceding 3 months as risk factors for BnESBL-E-BSI-related mortality, while receipt of carbapenems within 72 hours of symptom onset improved survival(OR, 0.128; 95% CI, 0.018– 0.912; p = 0.04). BnESBL-E isolates demonstrated no clonal transmission and remained highly susceptible to amikacin, carbapenems and tigecycline. Coexistence of multiple ESBL types was frequently observed, occurring in 40.6% of BnESBL-Ec and 72.7% of BnESBL-Kp isolates.Conclusion: Given the high prevalence and mortality of BnESBL-E-BSI, carbapenems may be preferable treatment option for non-urinary ESBL-E-BSIs. BnESBL-E represents an underestimated clinical threat, warranting timely identification of risk factors and the consideration of appropriate empirical therapy.Keywords: extended spectrum β-lactamase, β-lactam/β-lactamase inhibitors combinations, bloodstream infections, Enterobacteriaceae